SUSTAINABILITY PREDICTION BY EVALUATING THE EMERGY OF A CO-TREATMENT SYSTEM FOR MUNICIPAL WASTEWATER AND ACIDIC WATER USING INTERMITTENT ELECTROCOAGULATION - BRAVO-TOLEDO, LUIGI (2024)
THE OBJECTIVE OF THIS RESEARCH WAS TO EVALUATE THE SUSTAINABILITY OF A CO-TREATMENT SYSTEM THAT COMBINES MUNICIPAL WASTEWATER (MW) AND ACID MINE DRAINAGE (AMD) THROUGH THE TECHNIQUE OF INTERMITTENT ELECTROCOAGULATION, APPLIED AS AN ADVANCED SOLUTION TO IMPROVE CONTAMINANT REMOVAL EFFICIENCY AND OPTIMIZE ENERGY BALANCE. FOUR SCENARIOS WERE ANALYZED: TREATMENT I (WITH A 1/7 RATIO OF URBAN WASTEWATER TO AMD), TREATMENT II (WHICH INCLUDES AN ARTIFICIAL WETLAND), TREATMENT IIIA (WHICH INTRODUCES ELECTROCOAGULATION TO ENHANCE SULFATE REMOVAL AND PH REGULATION), AND TREATMENT IIIB (WHICH EMPLOYS A 1/15 RATIO OF AMD TO EUTROPHIC WATER). THE METHODOLOGY FOCUSED ON CALCULATING KEY SUSTAINABILITY INDICATORS SUCH AS THE NET YIELD RATIO (EYR), EMERGY INVERSION RATIO (EIR), ENVIRONMENTAL LOADING RATIO (ELR), AND SUSTAINABILITY INDEX (SI), IN ORDER TO ASSESS THE IMPACT OF EACH TECHNOLOGY ON THE ENERGY EFFICIENCY AND ENVIRONMENTAL LOAD OF THE SYSTEM. THE RESULTS SHOWED THAT, ALTHOUGH TREATMENT IIIA WAS EFFECTIVE IN CONTAMINANT REMOVAL, THE EIR INCREASED TO 0.18 AND THE ELR ROSE TO 0.62, INDICATING A HIGHER RELIANCE ON NON-RENEWABLE INPUTS DUE TO INCREASED ENERGY DEMAND. HOWEVER, TREATMENT IIIB, WHICH COMBINES ELECTROCOAGULATION WITH EUTROPHIC WATER, SIGNIFICANTLY IMPROVED THE SUSTAINABILITY OF THE SYSTEM, ACHIEVING AN SI OF 2.31 AND AN ELR OF 1.22, REFLECTING A REDUCTION IN ENERGY EFFICIENCY DUE TO INTENSIVE USE OF EXTERNAL RESOURCES, BUT OVERALL GREATER SUSTAINABILITY COMPARED TO THE OTHER SCENARIOS. THIS RESEARCH CONCLUDES THAT INTERMITTENT ELECTROCOAGULATION, WHEN INTEGRATED WITH SYNERGISTIC RESOURCES LIKE EUTROPHIC WATER, CAN ENHANCE CONTAMINANT REMOVAL EFFICIENCY AND IMPROVE THE USE OF RENEWABLE RESOURCES, MINIMIZING ENVIRONMENTAL LOAD AND INCREASING THE SUSTAINABILITY OF WASTEWATER TREATMENT SYSTEMS. © 2024 BY THE AUTHORS.